2001
DOI: 10.1161/01.str.32.5.1116
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Homocysteine Levels and Risk of Silent Brain Infarction in Elderly People

Abstract: Background and Purpose-Silent brain infarction (SBI) on MRI is common in elderly people, and recent studies have demonstrated that SBI increases the risk of progression to clinically apparent stroke and cognitive decline. Therefore, an early and accurate detection of SBI and a search for potential treatable risk factors may have a significant impact on public health. Methods-Community-dwelling elderly people aged Ն66 years who participated in the present study (nϭ153) underwent brain MRI and standardized physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
3
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 32 publications
9
107
3
2
Order By: Relevance
“…This finding is concordant with previous findings from clinical studies that homocysteine levels were higher in patients with subcortical vascular encephalopathy, a type of dementia with subcortical diffuse white-matter lesions or *Adjusted for hypertension status, BMI, current alcohol intake, cigarette smoking status, serum total cholesterol levels, log-transformed triglyceride levels, quartiles of C-reactive protein, and serum glucose category as well as matching for sex, age, community, year of serum stored, and fasting status. multiple subcortical lacunae, 24 and patients with silent brain infactions 25 than in control subjects. These clinical manifestations involve the cerebral microvascular system.…”
Section: Iso Et Al Homocysteine and Risk Of Stroke In Japanese 2769mentioning
confidence: 78%
“…This finding is concordant with previous findings from clinical studies that homocysteine levels were higher in patients with subcortical vascular encephalopathy, a type of dementia with subcortical diffuse white-matter lesions or *Adjusted for hypertension status, BMI, current alcohol intake, cigarette smoking status, serum total cholesterol levels, log-transformed triglyceride levels, quartiles of C-reactive protein, and serum glucose category as well as matching for sex, age, community, year of serum stored, and fasting status. multiple subcortical lacunae, 24 and patients with silent brain infactions 25 than in control subjects. These clinical manifestations involve the cerebral microvascular system.…”
Section: Iso Et Al Homocysteine and Risk Of Stroke In Japanese 2769mentioning
confidence: 78%
“…[29][30][31][32][33][35][36][37][38][39][40][41] These studies reported an increased risk in many individuals categorized as falling within the 'normal' range using the cutoff level of 15 mmol/l, particularly in those with homocysteine levels higher than 10 mmol/l. [29][30][31][32][33][35][36][37][38][39][40][41] For example, Malinow et al 29 have reported an increased risk of intima-media thickening in subjects with homocysteine levels higher than 10.5 mmol/l and Selhub et al 30 have reported a higher risk of extracranial carotid artery stenosis in subjects with homocysteine concentrations above 11.3 mmol/l. In the same context, Perry et al 31 have reported an about two-fold increase in the risk of stroke in middle-aged British men with homocysteine concentrations higher than 12.5 mmol/l and Giles et al 32 have reported an increased risk of nonfatal stroke in US adults with homocysteine levels above 12 mmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, various studies have demonstrated an association between homocysteine levels and cerebral, coronary and peripheral vascular disease in both men and women. [29][30][31][32][33][34][35][36][37][38][39][40][41] This association is usually consistent, strong, dose-related and biologically plausibile. [29][30][31][32][33][34][35][36][37][38][39][40][41] Some mechanisms have been suggested to explain the increased vascular risk associated with higher homocysteine levels.…”
Section: Introductionmentioning
confidence: 99%
“…There is no definite data on the relationship between cerebral arteriosclerosis and cholesterol. Cerebrovascular disorder plays an important role in pneumonia, and in the case of cerebrovascular disorder, the value of homocysteine is more significant factor than cholesterol (38). It is already known that vitamin B12 and folic acid metabolize homocysteine (39).…”
Section: Prevent Cerebrovascular Disordermentioning
confidence: 99%